Molecular imaging is non-inferior to adrenal vein sampling for diagnosing surgically curable primary aldosteronism: a prospective, within-patient study - Xilin Wu; Alasdair McIntosh; Alex McConnachie; Mark Gurnell; William M Drake; Morris J Brown (Efficacy and Mechanism Evaluation)
Background Primary aldosteronism due to a unilateral aldosterone-producing adenoma is a common cause of hypertension. This can be cured or greatly improved by adrenal surgery. However, the invasive nature of the standard presurgical investigation contributes to fewer than 1% of patients with primary aldosteronism being offered the chance of a cure. Objectives The primary objective of our prospective study was to compare the accuracy of a non-invasive test, [11C]metomidate positron emission tomography computed tomography scanning, with adrenal vein sampling in predicting the biochemical remission of primary aldosteronism and the resolution of hypertension after surgery. Design and methods All participants of the study underwent both investigations, in random order, as determined by minimisation. Individuals were recommended for surgery if one or both investigations indicated unilateral primary aldosteronism. Biochemical and clinical outcomes were assessed at 6 months post surgery, or after 9–12 months of medical therapy. In November 2019, the MATCH extension study was added to address two study limitations. Firstly, the short (20-minute) half-life of [11C]-metomidate, which currently limits its use to centres with an on-site cyclotron. Secondly, the short, 6-month interval between surgery and primary outcome determination. Development of para-chloro-2-[18F]fluoroethyletomidate, an 18F analogue of [11C]-metomidate with a 109-minute half-life, allowed an within-patient comparison of para-chloro-2-[18F]fluoroethyletomidate and [11C]metomidate positron emission tomography in 31 participants in the extension study. The extension also allowed assessment of outcomes at 2 years post intervention. Results In the original MATCH study, a total of 128 patients reached 6- to 9-month follow-up, with 78 (61%) treated surgically and 50 (39%) managed medically. The accuracies of [11C]metomidate positron emission tomography and computed tomography at predicting biochemical and clinical success following adrenalectomy were, respectively, 72.7% and 65.4%. For adrenal vein sampling, the accuracies were 63.6% and 61.5%. [11C]metomidate positron emission tomography and computed tomography was not significantly superior, but the differences of 9.1% (95% confidence interval −6.5% to 24.1%) and 3.8% (95% confidence interval −11.9% to 9.4%) lay within the pre-specified−17% margin for non-inferiority (p = 0.00055 and p = 0.0077, respectively). At 2 years post surgery, partial/complete or complete clinical success were achieved in 78/96 (81%) and 24/96 (25%) of patients, respectively. Comparing patients whose systolic blood pressure was ≤ 135 or > 135 mmHg on spironolactone, complete clinical success occurred in 9/19 and 6/44, respectively (odds ratio 5.7, 95% confidence interval 1.6 to 19.8; p = 0.008); 10/14 (71%) patients harbouring KCNJ5 mutations achieved complete clinical success at 2 years (odds ratio 16.9, 95% confidence interval 3.5 to 80.7; p = 0.0002), compared with 0/16 with CACNA1D and 4/15 with other mutations. There was high agreement in prediction of unilateral primary aldosteronism: [11C]metomidate positron emission tomography and computed tomography 18/31 (58.1%), para-chloro-2-[18F]fluoroethyletomidate 17/31 (54.8%), κ = 0.850, 95% confidence interval (0.676 to 1.000). Limitations  Accuracy of [11C]metomidate positron emission tomography and computed tomography and adrenal vein sampling could only be assessed in the surgical group. The assumption was made that if both investigations indicated bilateral disease, this was accurate; which is a limitation of the study. Furthermore, the accuracy of para-chloro-2-[18F]fluoroethyletomidate was assessed against [11C]metomidate positron emission tomography, which we know from the overall study is not perfect as a small proportion of aldosterone-producing adenomas were diagnosed by only one investigation. Further work is required to ascertain reasons for this discrepancy. Conclusions  Overall, [11C]metomidate positron emission tomography is non-inferior to adrenal vein sampling in detecting unilateral primary aldosteronism. Favourable clinical Primary Aldosteronism Surgical Outcome study outcomes seen at 6 months post adrenalectomy are sustained at 2 years and are predicted by genotype and preoperative response to spironolactone. Para-chloro-2-[18F]fluoroethyletomidate is a valid alternative to [11C]metomidate positron emission tomography in primary aldosteronism subtyping. Funding This synopsis presents independent research funded by the National Institute for Health and Care Research (NIHR) Efficacy and Mechanism Evaluation programme as award number 14/145/09. Plain language summary Hypertension (high blood pressure) causes heart attacks and strokes. The commonest curable cause of hypertension is primary aldosteronism, where excess production of the hormone aldosterone from one/both adrenal glands leads to an excess of sodium (salt) in the body. In approximately half of cases the cause is a benign tumour, an aldosterone-producing adrenal adenoma, which can be removed by surgery. However, the current diagnostic test (adrenal vein sampling) for such a tumour is difficult, invasive and only available at a handful of centres in the UK. This, with several other factors not addressed in this study, contributes to only 1% of patients with primary aldosteronism being appropriately investigated and treated. [11C]-Metomidate positron emission tomography and computed tomography is a new scan which will light-up if an aldosterone-producing adenoma is present. The aim of the MATCH study was to compare the accuracy of [11C]metomidate positron emission tomography and computed tomography with adrenal vein sampling. One disadvantage of [11C]metomidate positron emission tomography and computed tomography is the radioactivity from the tracer given during the scan has a short half-life, meaning the scan can only be performed where there are facilities to manufacture the tracer on site. A similar scan using a dye with a much longer half-life (para-chloro-2-[18F]fluoroethyletomidate positron emission tomography and computed tomography) was developed more recently, therefore in the MATCH extension study 31 participants had an additional para-chloro-2-[18F]fluoroethyletomidate positron emission tomography and computed tomography scan to allow comparison with [11C]metomidate positron emission tomography and computed tomography. We also looked for clues which could help predict which individuals were more likely to be cured by surgery. The MATCH study demonstrated that [11C]metomidate positron emission tomography and computed tomography is as accurate as adrenal vein sampling in diagnosing patients with PA confined to one adrenal. Para-chloro-2-[18F]fluoroethyletomidate positron emission tomography and computed tomography gave equivalent imaging data as [11C]metomidate positron emission tomography and computed tomography, suggesting that it is also a valid alternative to adrenal vein sampling. Participants whose blood pressure responded well to spironolactone (medication which blocks aldosterone) were more likely to be pill-free at both 6 and 24 months after surgery. Certain gene mutations (DNA ‘spelling mistakes’) in aldosterone-producing adenomas were associated with cure of hypertension: KCNJ5 and GNA&CTNNB1; while others (CACNA1D mutations) were associated with poorer outcomes.